2018
DOI: 10.1155/2018/1542602
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, Anti-Inflammatory, and Antitumoral Effects of Aqueous Ethanolic Extract fromPhoenix dactyliferaL. Parthenocarpic Dates

Abstract: The aim of this study was to evaluate the antioxidant, the anti-inflammatory, and the antitumoral activities of the aqueous ethanolic extract from Phoenix dactylifera L. parthenocarpic dates. The antioxidant activity was carried using DPPH radical scavenging activity. The result showed that parthenocarpic dates had strongly scavenging activity on DPPH reaching 94% with an IC50 value of 0.15 ± 0.011 mg/mL (p < 0.05). The anti-inflammatory potential was determined by the inhibitory effect of the aqueous ethanoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 23 publications
(39 reference statements)
0
16
0
1
Order By: Relevance
“…Furthermore, the administration of these alcoholic extracts significantly enhanced the antioxidant level (Vitamin C, E, and A). EI Abed et al (2018) investigated the antimicrobial, anti‐inflammatory, and antioxidants potential of parthenocarpic dates extracts (water, ethanolic). These activities were determined through DPPH, phospholipase A 2 activity, and MTT test (3‐(4,5‐dimethylthiazol‐2‐yl)‐2,5‐diphenyltetrazolium bromide), respectively.…”
Section: Biological and Therapeutic Potential Of Datesmentioning
confidence: 99%
“…Furthermore, the administration of these alcoholic extracts significantly enhanced the antioxidant level (Vitamin C, E, and A). EI Abed et al (2018) investigated the antimicrobial, anti‐inflammatory, and antioxidants potential of parthenocarpic dates extracts (water, ethanolic). These activities were determined through DPPH, phospholipase A 2 activity, and MTT test (3‐(4,5‐dimethylthiazol‐2‐yl)‐2,5‐diphenyltetrazolium bromide), respectively.…”
Section: Biological and Therapeutic Potential Of Datesmentioning
confidence: 99%
“…Worldwide, more than 3000 date cultivars are known [12]. Saudi Arabia has a rich diversity of date cultivars of which Khalas, Sheshi, and Reziz are well known, especially in the Eastern Province of the Kingdom [13][14][15][16][17]. Although date pits represent around 11-18% of date fruit, they are considered of low market value due to their hard texture and contamination by fungi or insects during the processing of date fruits [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…However, the standard ascorbic acid recorded an IC 50 of 22.72µM (12µg). A report on date palm fruit conducted by El Abed et al [26] stated that the ethanolic extract of the fruit showed strong activity against DPPH and showed an IC 50 of 0.15±0.011mg/mL. On the other hand, the methanolic extracts of Deglet Nour, Medjhoul, and Barhee date palm leaves showed an IC 50 of 2.08, 2.11, and 2.14 mg/mL respectively when Gallic acid was used as standard [21].…”
Section: Dpl Scavenging Activity Against Dpph Radicalmentioning
confidence: 99%